Potential influence on drug efficacy from interaction of tartrazine and trypsin. Issue 6 (3rd July 2018) - Wang, Chun-Dan; Liu, Bao-Sheng; Bian, Gang; Ma, Li-Hua; Zhang, Hong-Cai; Cheng, Xu
Abstract: The extent to which drugs combine with trypsin is influenced by the interaction of tartrazine and trypsin, which may cause overdose or underdose of drugs. Therefore, the interaction of tartrazine and trypsin is investigated by methods of spectrometry in this paper. The binding rate of tartrazine to trypsin is 80.95–95.71% at 310 K, and Hill's coefficients are almost 1. The effect of tartrazine on trypsin structure was studied by synchronous and circular dichroism. The results showed that the binding of tartrazine and trypsin induced the conformational change of trypsin, and quenched the endogenous fluorescence in trypsin. The results of molecular docking revealed that tartrazine is located in the catalytic active site of trypsin, and is consistent with that of experimental calculation.